Nitric Oxide Manipulation: A Therapeutic Target for Peripheral Arterial Disease? - Gareth Williams; Xu Shi-Wen; David Abraham; Sadasivam Selvakumar; Daryll M. Baker; Janice C. S. Tsui (Cardiology Research and Practice)
Peripheral Arterial Disease (PAD) is a cause of significant morbidity and mortality in the Western world. Risk factor modification and endovascular and surgical revascularisation are the main treatment options at present. However, a significant number of patients still require major amputation. There is evidence that nitric oxide (NO) and its endogenous inhibitor asymmetric dimethylarginine (ADMA) play significant roles in the pathophysiology of PAD. This paper reviews experimental work implicating the ADMA-DDAH-NO pathway in PAD, focussing on both the vascular dysfunction and effects within the ischaemic muscle, and examines the potential of manipulating this pathway as a novel adjunct therapy in PAD.